Associations between self-reported symptoms of prenatal maternal infection and post-traumatic stress disorder in offspring: Evidence from a prospective birth cohort study - Betts, K.; Salom, C.; Williams, G.; Najman, J.; Alati, Rosa (Elsevier BV, 2015)
© 2015 Elsevier B.V. All rights reserved. Objective Consistent evidence has linked a range of prenatal maternal infections with psychotic disorders in later life. However, the potential for this exposure to impact more common disorders requires further investigation. Methods Participants came from the Mater University Study of pregnancy, a longitudinal, pre-birth cohort study which recruited pregnant mothers from a Brisbane hospital between 1981 and 1984. At age 21, 2439 offspring completed the CIDI-Auto. Multivariate logistic regression was used to investigate associations of self-reported symptoms of prenatal infection with a range of DSM-IV anxiety and affective diagnoses, while also testing for gender interactions. Results In multivariate analyses, self-reported symptoms of prenatal genital infection predicted Post-traumatic stress disorders (OR=2.38, 95% CI: 1.14, 4.95) and social phobias (OR=1.93, 95% CI: 1.03, 3.61), in addition to evidence for a gender interaction by which males (OR=6.04, 95% CI: 2.00, 18.30) but not females were at greater risk for PTSD. Further analyses among those with PTSD revealed the relationship to be stronger when excluding those not exposed to trauma (OR=3.21, 95% CI: 1.53, 6.72). Limitations We were unable to clinically or serologically verify the presence and the type of prenatal genital infection. Conclusion This is the first study to show an association between self-reported symptoms of prenatal genital infections and two highly prevalent anxiety disorders among adult offspring. The relationship with PTSD was particularly strong and suggested that the exposure may primarily impact PTSD in males. Further research with the capacity to assess a fuller-range of specific prenatal infections is warranted to evaluate the potential of reducing the prevalence of these disorders.